Musik Ritual"TARAWANGSA" di Desa Rancakalong,Kabupaten Sumedang, Jawa barat - Cucup Cahripin (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2008)
Indonesian people consist of many kind of tribes. Each ethnic has hereditary cultural tradition. In West Java, most of the society is Sunda Ethnic, so their culture is â€œSUDANESEâ€, included the language, traditional art which has their own characteristic and itâ€™s defferent from the other ethnic. Essspecially, Rancakalong society in Sumedang has hereditary ritual tradition and itâ€™s colled jentreng-Ngek-Ngek, because the music instrumental used in ritual ceremony consist of one strings instrumental, named KACAPI and rubs instrumental named TARAWANGSA. So the public society usually call it â€œTARAWANGSA The poins of this exotics traditional art Tarawangsa is a ritual ceremony to respect Rice-plants Goddess, or DEW! SRI, who believes as a Goddess, that bless the rice plants ftrtility. So, this ritual ceremony held when harvest comes. This Tarawangsa has some values. They are praying to god almighty, solidarity, dance art, music art, performing art, attraction for tourism and etc. Also the import tant, it can bring up the unity and society as Indonesia people by taking possesion of it, taking care of it, and developing ii. By Individually, they feel sates fled, it erashes in the incrassiation of prosperity mentally spiritually, and physically material, and also esthetic valve. This spirit also can be in crease the production of food, so that â€œthe defence of foodâ€ increases.Keyword : Rice-plant Goddess, God almighty, solidarity, Performing art, and defence of food